Assessing how an adaptive management approach was incorporated in the mitigation strategies for acid mine drainage discharge in the Witwatersrand basin - Rantsieng, Masekantsi Rahab (My University, 2018)
The predicaments faced by humanity today differ from the past due to the increasing scale of human influence, complexities and uncertainties (Allen et al., 2010), which limit management options. Adaptive management is based on the philosophy that knowledge is incomplete i.e. there will always be uncertainty and unpredictability in the behaviour and dynamics of complex social-ecological systems. Given the complexity of the South African mining industry, this research aimed to explore the link between management and science by assessing the extent to which an adaptive management approach had been incorporated into short-term and long-term mitigation strategies for the discharge of acid mine water in the Witwatersrand Basin. The methodology included a review of the adopted mitigation strategy document, a literature review of adaptive management literature and an in-depth analysis of a case study using nine interviews, conducted with key informants and contributors from the government, an educational institution, industry (mines currently dealing with the issue), and civil society. An inductive and descriptive approach was followed to gather and analyse data to formulate answers to the research questions. The findings of the study indicated that the efforts that went into designing the short-term solutions were limited due to the lack of communicating amongst stakeholders and the failure to incorporate a value-based approach. Results also showed that complexities and uncertainties were not addressed to allow for adaptation to constant change. It was found that the short-term interventions had no managerial flexibility which limited learning. Insufficient monitoring and a lack of transparency regarding the dissemination of monitoring results were highlighted. Moreover, experimental efforts were limited due to lack of capacity and funding. In conclusion, although the long-term strategy incorporated some aspects of adaptive management, the short-term mitigation measures were reactive rather than proactive. It is recommended that on-going training and good communication are maintained amongst stakeholders. Recommendations for economic constraints include the sharing of costs through partnerships, evaluating trade-offs between costs and effectiveness and investigating cheaper measuring methods for monitoring. Risk-averse initiatives such as conducting risk assessments during pilot studies and accommodating for different project scales can be employed to mitigate against resources that are sensitive to change.
School of Mining Engineering, Centre for Sustainability in Mining and Industry, University of the Witwatersran, 2018
Keywords: Acid mine drainage; Coal mines and mining--South Africa